Analyzing the Impact of Collaborative Strategy on Students’ Reading Comprehension - Marreta Putri Zenawati; Indri Astutik; Fitrotul Mufaridah (JELP Journal of English Language and Pedagogy, 2025)
The most crucial skill that must be mastered by everyone to increase their knowledge is reading. One way to obtain media information is by reading since many books are written in English. The difference between this research and previous research is the previous research concentrated on writing. Therefore, it is important to do research entitled “Analyzing the impact of collaborative strategy on students’ reading comprehension while this research implemented to reading comprehension for Junior High School students with the help of learning as a support material delivery. in narrative text”. The problem of this research is whether is there any significant effect of the use of collaborative strategy reading on students’ reading comprehension SMP Negeri 2 Balung Jember grade (9) academic year 2023/2024”. The research adopts a quasi-experimental approach. The research subject is ninth grade consisting of 31 students. The data are collected using test method, and the instrument used is reading test. In order to analyse the data student’s reading score percentage formula is used. Based on the post-test results, the experimental group (IX H) achieved an average score of 75.81. The independent T-test results indicate a significant difference with a value of 0.000. Based on the research results, it can be concluded that collaborative strategy method is able to improve the student’s reading comprehension at SMP Negeri 2 Balung Jember grade (9) academic year 2023/2024”.